2007
DOI: 10.1111/j.1440-1746.2007.05039.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the M2A patency capsule for diagnosis of critical intestinal patency: Results of a prospective clinical trial

Abstract: The M2A PC is a reliable indicator of functional patency in suspected or even known cases of intestinal stricture. It could be used prior to conventional capsule endoscopy to predict and minimize the risk of impaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
1
28
0
3
Order By: Relevance
“…Thus, the technique is not without risk of complications. Indeed, retention of the capsule was observed in more than 10% of the patients with Crohn's disease (72). However, video capsule endoscopy is a highly promising technique whose exact role in IBD will have to be determined.…”
Section: Ibdmentioning
confidence: 99%
“…Thus, the technique is not without risk of complications. Indeed, retention of the capsule was observed in more than 10% of the patients with Crohn's disease (72). However, video capsule endoscopy is a highly promising technique whose exact role in IBD will have to be determined.…”
Section: Ibdmentioning
confidence: 99%
“…Several studies have highlighted the value of these capsules in assessing functional patency of the gut lumen. 15,16 Our patient did not undergo a preliminary investigation with a patency capsule and there is good evidence in the literature to suggest that such an investigation would have highlighted an underlying obstructive pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of the initial model has been questioned (Gay, 2005), but recently, a new patency capsule model with a biodegradable body has been developed. The new patency capsule is a reliable indicator of functional patency in suspected or even known cases of intestinal stricture, and it can be used prior to conventional CE to predict and minimize the risk of retention and impaction (Banerjee, 2007). As another rare condition, a previous study reported that a patient having a nervous temperament showed the discomfort, headache, and low blood pressure 2 h after capsule ingestion (Tokuhara, 2010).…”
Section: Complicationsmentioning
confidence: 99%